Inovasi Manajemen Kelas dan Etos Kerja Guru PAI di Era Kurikulum Merdeka - Anwar, Anwar; Hermawansyah, Hermawansyah; Junaidin, Junaidin (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2025)
Classroom management and the work ethic of Islamic Religious Education (IRE) teachers are two key factors in creating effective learning, especially in the era of the Merdeka Curriculum, which emphasizes student independence and active participation. This study aims to analyze the implementation of classroom management, the work ethic of PAI teachers, and their implications for the effectiveness of the learning process at the Muhammadiyah Riung Private Madrasah Aliyah. The study uses a qualitative approach with a case study method, while data is obtained through observation, interviews, and documentation, then analyzed through reduction, display, and conclusion drawing. The results of the study show that: (1) classroom management is carried out through the adaptive management of space, time, discipline, and teacher-student interaction; (2) the work ethic of PAI teachers is reflected in their professionalism, discipline, commitment, and moral exemplarity; (3) the effectiveness of learning is characterized by increased motivation, student involvement, and the use of interactive methods and digital technology. The novelty of this study lies in the combination of classroom management analysis and PAI teachers' work ethic as an integrated strategy to improve learning effectiveness, which can be used as a model for developing the quality of Islamic education in madrasahs.